Edukasi Kandungan Antioksidan Kombinasi Daun Pegagan dan Mint sebagai Alternatif Minuman Herbal - Padmiswari, Anak Agung Istri Mas; Wulansari, Nadya Treesna; Harditya, Kadek Buja (Pakis Journal Institute, 2025)
An unhealthy lifestyle, such as poor diet and lack of physical activity, increases the risk of degenerative diseases due to oxidative stress caused by free radicals. Antioxidants play a crucial role in neutralizing free radicals and protecting cells from damage. Gotu kola and mint leaves are known to contain high levels of antioxidants; however, their use as an herbal beverage remains underutilized. This study aims to enhance public understanding of the benefits of combining gotu kola and mint leaf extracts and to promote their consumption as a natural herbal drink. The methods used include a pretest, direct material presentation with leaflets, and a posttest. The pretest results indicated low to moderate initial knowledge among participants. After the session, posttest results showed a significant improvement in understanding. This education effectively increased public awareness of natural ingredients for a healthy lifestyle. Similar initiatives should be conducted continuously.